Factors affecting satisfaction with treatment in European women with chronic constipation: An internet survey - Emmanuel, Anton (SAGE Publications, 2013)
BACKGROUND: Data on factors affecting treatment satisfaction in European women with chronic constipation are limited. OBJECTIVE: To assess factors associated with treatment satisfaction among European women with chronic constipation. METHODS: A 2011–2012 internet survey was conducted in men and women from 12 European countries. Respondents analysed were female with self-reported chronic constipation (≥1 symptoms for ≥6 months of lumpy/hard stools, feeling of incomplete evacuation, and pain during defecation, as well as <3 bowel movements/week). For laxative users, satisfaction with treatment, factors affecting satisfaction, and interactions with healthcare professionals were collected. RESULTS AND CONCLUSIONS: In total, 4805/50,319 participants fulfilled the inclusion criteria (female with chronic constipation). Of the laxative users (1575/4805), 57% (n = 896) were satisfied with their treatment, while 26% were neutral, and 17% dissatisfied. Dissatisfied respondents visited their GP less frequently in the past 12 months, were more likely to obtain over-the-counter laxatives, and took a dose higher than recommended more frequently than those satisfied. Respondents were most satisfied with ease of use of treatment and least satisfied with relief from bloating. Newer treatments aimed at alleviating symptoms, particularly bloating, are required for respondents neutral or dissatisfied with their current treatment.